The Relationship Between Physiological Factors and Psychosocial Factors in The Work Environment on Employee Performance - Fariz Husaini; Samsul Hilal; Eko Mirsiyanto (Jurnal Ilmu Kesehatan Masyarakat Berkala, 2021)
The work environment can be said to be good or appropriate if the people in it can carry out activities optimally, healthy and comfortable. A safe and healthy work environment is proven to have an effect on work productivity. This study uses a quantitative analytical descriptive type with a cross sectional. The population in this study is all employees who work at Kambang General Hospital. In 2021 as many as 77 people. On 20 on 27 August 2021. The sample as 55 respondents. The sampling method is total sampling. The results showed that there was a significant relationship between Physiological Factors (p-value = 0.006), Psychosocial Factors (p-Value = 0.007) on employee performance at Kambang General Hospital, Jambi City in 2021. With the results of the Chi-Square statistical test, the value obtained was p-value < 0.05. Efforts can be made to improve performance by, as well as providing a reward system in the form of material or appreciation of work results to increase motivation for workers and create more active communication between management and workers.